Super (a; d) - Face Antimagic Total Labeling of Connective Shackle Graph (C5; e; n) - Siska Binastuti; Dafik Dafik; Arif Fatahillah (jcgant, 2020)
Let G be a simple graph of order p, size q and face r. The graph G is called a super (a; d) - face antimagic total labeling , if there exist a bijection f : V (G) [ E(G) [ F (G) ! f1; 2; :::; p + q + rg such that the set of s-sided face weights, Ws = fas; as + d; as + 2d; :::; as + (rs ¡1)dg form an arithmetic sequence with ¯rst term a,common di®erence d, where a and d are positive integers s and rs is the number of s-sided faces. Such a graph is called super if the smallest possible labels appear on the vertices. The type of Face Antimagic Labeling is (1,1,1). In this paper, describe of Super (a; d) - Face Antimagic of Connective Shackle (C5; e; n) Graph. Keywords: Super (a; d)-face antimagic total labeling, face antimagic la-beling.